2017
DOI: 10.1016/j.jmb.2017.06.007
|View full text |Cite
|
Sign up to set email alerts
|

HnRNP A1 Alters the Structure of a Conserved Enterovirus IRES Domain to Stimulate Viral Translation

Abstract: Enteroviruses use a type I IRES structure to facilitate protein synthesis and promote genome replication. Type I IRES elements require auxiliary host proteins to organize RNA structure for 40S ribosomal subunit assembly. Heterogeneous nuclear ribonucleoprotein A1 stimulates Enterovirus 71 (EV71) translation in part through specific interactions with its stem loop II (SLII) IRES domain. Here, we determined a conjoined NMR-SAXS structure of the EV71 SLII domain and a mutant that significantly attenuates viral re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
95
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(97 citation statements)
references
References 83 publications
1
95
0
1
Order By: Relevance
“…MNK1 substrate hnRNPA1 has been shown to colocalize with viral nucleoprotein in the cytoplasm, particularly in the perinuclear region of virus-infected cells (Shi et al, 2000;Wang and Zhang, 1999) and is believed to regulates not only IRES-dependent translation initiation in enteroviruses (Tolbert et al, 2017), but also non-IRES-dependent translation initiation in SINV (Lin et al, 2009) and HCV (Kim et al, 2007;Li et al, 1997).…”
Section: Mnk1 In Initiation Of Cap-independent Viral Mrna Translationmentioning
confidence: 99%
“…MNK1 substrate hnRNPA1 has been shown to colocalize with viral nucleoprotein in the cytoplasm, particularly in the perinuclear region of virus-infected cells (Shi et al, 2000;Wang and Zhang, 1999) and is believed to regulates not only IRES-dependent translation initiation in enteroviruses (Tolbert et al, 2017), but also non-IRES-dependent translation initiation in SINV (Lin et al, 2009) and HCV (Kim et al, 2007;Li et al, 1997).…”
Section: Mnk1 In Initiation Of Cap-independent Viral Mrna Translationmentioning
confidence: 99%
“…Extensive studies of the EV71 IRES have revealed functional contributions of different RNA structures along with the collection of cellular proteins that interact with those structures [5][6][7][8][9][10][11][12][13][14][15] . Of particular importance, the stem loop II (SLII) domain interacts specifically with at least four cellular RNA binding proteins (RBPs) and a viral derived small RNA to modulate translation levels 5,7,9,10,16 . The secondary structure of the EV71 SLII domain folds into a phylogenetically conserved hairpin with a 7-nt apical loop and 5-nt bulge (Fig 1B) 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Of particular importance, the stem loop II (SLII) domain interacts specifically with at least four cellular RNA binding proteins (RBPs) and a viral derived small RNA to modulate translation levels 5,7,9,10,16 . The secondary structure of the EV71 SLII domain folds into a phylogenetically conserved hairpin with a 7-nt apical loop and 5-nt bulge (Fig 1B) 9 . The three-dimensional structure of SLII shows that the apical loop and bulge form well-defined structural motifs (Fig 1C) 9 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations